Promoting E-Commerce in Georgia : Exploring Constraints to Online Participation using Baseline Data from an Experimental Study - Apedo-Amah, Marie Christine (World Bank, Washington, DC, 2020)
E-commerce has the potential to expand market opportunities for businesses. However, it is not guaranteed. The World Development Report on Digital Dividends (World Bank 2016) highlights the importance of complementary analog support that may be needed to ensure people and businesses are able to fully benefit from the opportunities that high-speed, ubiquitous internet can provide. The first step in providing such support is understanding the constraints to adoption. The Competitive Policy Evaluation Lab (ComPEL) is supporting an impact evaluation in Georgia to generate knowledge about the constraints that prevent firms from participating in e-commerce platforms, while also testing an innovative approach to address the identified issues. The study evaluates the ‘Broadband for Development’ (BfD) project, a component of the World Bank-supported Georgia National Innovation Ecosystem (GeNIE) program, that aims to foster innovation, particularly for otherwise marginalized firms. The BfD provides support to Micro, Small and Medium Enterprises (MSMEs) located outside of the capital, Tblisi, to adopt broadband connections and establish an online retail presence through e-commerce training. Before BfD launched this effort, the research team collected and analyzed baseline data regarding 2,180 eligible firms. The purpose of this note is to explore the baseline results and some implications for BfD, or similar projects supported by the World Bank’s Finance, Competitiveness and Innovation (FCI) Global Practice, within the context of the impact evaluation.